The Gender-Based Influence of Project and Montessori Learning on Bullying in Children - Septriyani, Septriyani; Hartati , Sofia; Meilanie , R. Sri Martini (Aulad: Journal on Early Childhood, 2024)
Bullying in early childhood education has become a growing concern due to its impact on children’s social, emotional, and cognitive development. This study investigates the effectiveness of Project-Based Learning (PjBL) and Montessori methods in reducing bullying behaviors among children aged 5-6 years, with a focus on gender differences. Both PjBL and Montessori approaches were applied to address verbal and non-verbal bullying, which manifests differently in boys and girls. PjBL, which emphasizes collaboration and teamwork, was found to significantly reduce physical bullying, particularly among boys, while the Montessori approach, with its focus on empathy, self-regulation, and structured learning, was more effective in reducing verbal and relational bullying, particularly among girls. The study employed a quantitative experimental design, using pre-tests and post-tests to measure bullying behavior across experimental and control groups, and utilized a 2x2 factorial ANOVA to assess the interaction effects between teaching methods and gender. The results indicate that both educational strategies effectively reduced bullying behaviors, with significant gender-specific effects. These findings suggest that integrating PjBL and Montessori methods, tailored to the unique developmental needs of boys and girls, can create a more inclusive and supportive learning environment that mitigates bullying behaviors. The implications of this research highlight the importance of gender-sensitive educational interventions in fostering positive social and emotional development in early childhood education